THE INFLUENCE OF PEER TUTORING MODEL ON THE PROBLEM-SOLVING UNDERSTANDING AND COMMUNICATION SKILLS OF EIGHT GRADE JUNIOR HIGH SCHOOL STUDENTS - Teguh Rizki Andriana; Jozua Sabandar; Mumun Syaban ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
Various efforts to develop education which related to quality of education were overall implemented by the government to enhance quality of education. The implementation of compatible method was an effort to improve learning achievement and accomplish learning goals. Peer tutoring is a group of students who have completed learning material then provide assistance for others who got difficulty in understanding the material. From the research result were obtained, (1) Sig. 0,011 = Ho was rejected means there was difference in students learning result in mathematic lesson by using peer tutoring method compare with conventional learning method; (2) Sig. 0,002 = Ho was rejected means there was difference in problem solving communication skill in mathematic lesson by using peer tutoring method compare with conventional learning method; (3) Sig. 0,043 = Ho was rejected means there was difference in problem solving comprehension skill in mathematic lesson by using peer tutoring method compare with conventional learning method. From the data, it can be concluded that students learning result using peer tutoring method was more effective. It was because, this method demanded students to be more active in learning process either individual or overall.